Human Rights: Negative and Affirmative Aspects of Environmental Justice - Mehdi, Abasi Sarmadi; Khomami, Reza Asadi (European Journal of Social Science Education and Research, 2022)
After Second World War by establishment United Nation, to support of right of life, survives and peace for human, Universal Declaration of Human Rights was issued. In later years, second and third generations of human rights were established which respect for human rights is obligatory for member states.Environmental destruction as outcome of Progression of industry and technology, is another important problem which is outshining human life. In the second half of the twentieth century, several international conventions were formed in order to protecting the environment and preventing its destruction. On the other hand, in the United States, The civil rights movement in the 60s was the source of another movement called environmental justice. At the international level, In the 90s of the twentieth century coincided with the UN plan for sustainable development, the environmental justice movement arose. With the start of the twenty first century, environmental activists and followers of the environmental justice movement found out the common points of environmental justice and issues raised in the generations of human rights and attempts to link these two movements and beginning to find their common points. In the second half of twenty century. With increasing of activity of United Nation many conventions were ratified by countries that guarantee some rights of people but conventions about human rights and environment were separated. This article examines positive and negative characteristics governing environmental justice in comparison with the international documents.
Keywords: Environmental justice; Universal Declaration of Human Rights; Sustainable development; international conventions; United Nation